IMPLEMENTASI MEDIA DIGITAL UNTUK PERKEMBANGAN BAHASA INGGRIS ANAK USIA DINI - Yoga Purandina I Putu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
This study aimed to investigate the phenomenon about implementation of digital media suporting the development of English Language in early childhood students at Tunas Mekar Kindergarten Tegaljadi Village. This study find out perceptions of teachers, children, and parents regarding the how was the implementation process of digital media suporting English developmet in early childhood students in Tunas Mekar Tegaljadi Village, and to determine the perception of teacher and parents how efective digital media supporting English development in early childhood students at Tunas Mekar Tegaljadi Village. This research is a qualitative research using descriptive method with observation sheets and interview guides to teachers, children, and parents. As for the results, first, In general, it runs smoothly through three processes, namely the preparation process, activities, and evaluation. At each stage this has been carried out optimally by teachers and students who are accompanied by their parents. Second, learning English through digital media has also been able to improve the development of early childhood English in TK Tunas Mekar II. They have been able to pronounce simple vocabulary in English. Able to say greetings and be able to follow orders through verbs in English. Besides that, the children did this activity with great enthusiasm and fun.